Social media in use: A uses and gratifications approach - Visar Rrustemi; Egzona Hasani; Gezim Jusufi; Dušan Mladenović (Management : Journal of Contemporary Management Issues, 2021)
Information technologies have caused radical changes in many areas, they have also changed marketing activities. Today, marketing activities are carried out in digital environments, facilitating the work of companies and helping consumers around the world. Consumers get the right information and data about products and services much easier and faster, as well as access different forms of entertainment. Therefore, it can be said that the place of traditional marketing today has been replaced by digital marketing. This paper tries to shed some light on how consumers of Western Balkans and specifically in Kosovo, use social media and how those shape their attitudes, based on the uses and gratifications approach. This is the first paper from this region, which analyzes social media, based on the previously mentioned approach. Since research in the region was prohibitive for us, we selected a sample of 200 consumers from Kosovo, active on social media. The findings of this paper serve managers in better attracting online customers through social media.